Managing contract manufacturing relationships - An explorative research framework - Tim Brandl (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: Contract manufacturing has established itself as a cornerstone of manufacturing practices across industries. The high degree of external value creation, operational interfaces, relational dynamics, and knowledge exchange coordination require demand-oriented management of contract manufacturing service providers from an outsourcing company's perspective. Methodology: An explorative research framework for managing contract manufacturing organizations (CMOs) is developed through a literature review on inter-organizational relationships (IOR) and empirical validation. The framework draws on contingency theory and complex adaptive systems theory as structural theories to support the research process. Findings: The need for a dedicated management approach of CMOs in distinction to other IORs is derived. The developed framework indicates the role of situational variables of contract manufacturing and their inherent dynamics for relationship management of CMOs. Originality: Despite the strong practical relevance, the literature on the management of IORs does not adequately address the phenomenon against the background of the distinctive management challenges of contract manufacturing. In relationship management, the developed framework systematically addresses these challenges because of the dynamic growth of the contract manufacturing market.
urn:nbn:de:gbv:830-882.0161700; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Advanced Manufacturing; Industry 4.0